Utilization of IP LM393 Sensor Module as an Automation System for a Portable Gallon Pump - Hardianto, Firman; Shofani, Maya; Kusuma, Hamdan Hadi (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
Research has been conducted on developing an automatic gallon pump based on the IP LM393 sensor. This research aims to provide alternative solutions to avoid direct contact as the cause of COVID-19 transmission. The research method used includes the stages of designing, manufacturing, and testing the automatic gallon pump based on the IP LM393 sensor. The results showed that installing IP LM393 in a portable gallon pump can help people avoid direct contact when pouring water. This research proves that some materials can be sensor barriers at specific distances with an effective light intensity range of 19-23 lux.